2004
DOI: 10.1113/jphysiol.2004.064816
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Serotonin and cholecystokinin synergistically stimulate rat vagal primary afferent neurones

Abstract: Recent studies indicate that cholecystokinin (CCK) and serotonin (5-hydroxytryptamine, 5-HT) act via vagal afferent fibres to mediate gastrointestinal functions. In the present study, we characterized the interaction between CCK and 5-HT in the vagal primary afferent neurones. Single neuronal discharges of vagal primary afferent neurones innervating the duodenum were recorded from rat nodose ganglia. Two groups of nodose ganglia neurones were identified: group A neurones responded to intra-arterial injection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 38 publications
0
18
0
1
Order By: Relevance
“…In examining the effects of CCK on feeding, many have suggested that the actions of CCK are partially dependent on 5-HT 3 receptor activation (1,6,14). Furthermore, primary vagal afferent neurons are potently stimulated by endogenous 5-HT and CCK release (26,53), and a subpopulation of nodose ganglion neurons possess high-affinity CCK 1 receptors and 5-HT 3 receptors (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In examining the effects of CCK on feeding, many have suggested that the actions of CCK are partially dependent on 5-HT 3 receptor activation (1,6,14). Furthermore, primary vagal afferent neurons are potently stimulated by endogenous 5-HT and CCK release (26,53), and a subpopulation of nodose ganglion neurons possess high-affinity CCK 1 receptors and 5-HT 3 receptors (24).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that CCK and 5-hydroxytryptamine (5-HT) act synergistically to activate vagal afferents (24). Early in vivo studies supported a role for 5-HT in the vasodilator responses elicited by CCK, secretin, or mucosal irritation (12).…”
mentioning
confidence: 99%
“…Transmitters released from the enteroendocrine cells in response to various stimuli, in addition to their paracrine actions on neighboring enterocytes, activate specific receptors within the enteric nervous system (15). Importantly, enteroendocrine cell products also activate receptors at afferent terminals in vagal and spinal pathways (10).…”
mentioning
confidence: 99%
“…Particular attention has been paid to the inactivation of intestinal neuroreceptors by 5-HT produced by EC cells and by CCK produced by enteroendocrine I cells. Furthermore, recent studies have shown that these two transmitters interact in stimulation of vagal primary afferent neurons (15). The transfer of information from the gut to the central nervous system has been the subject of theme articles in this journal (10,21).…”
mentioning
confidence: 99%
“…Similarly, 55% nodose neurones possessing high-affinity CCK-A receptors also responded to luminal perfusion of 5-HT. Interestingly, we showed that although a subthreshold dose of CCK-8 produced no measurable electrophysiological effects, it augmented the neuronal response to luminal 5-HT perfusion [118] (Fig. 3).…”
Section: Serotonin and Cholecystokinin Synergistically Stimulate Rat mentioning
confidence: 93%